Answer :

Given that,


f = {(1, 2), (3, 5), (4, 1) and g = {(2, 3), (5, 1), (1, 3)}


Now,


gof (1) = g(f(1)) = g(2) = 3


gof (3) = g(f(3)) = g(5) = 1


gof (4) = g(f(4)) = g(1) = 3


gof = {(1,3),(3,1),(4,3)}


fog (2) = f(g(2)) = f(3) = 5


fog (5) = f(g(5)) = f(1) = 2


fog (1) = f(g(1)) = f(3) = 5


fog = {(2,5),(5,2),(1,5)}


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar